Peningkatan Hasil Belajar dan Aktivitas Belajar Siswa Melalui Penggunaan Metode Demonstrasi Pada Mata Pelajaran Matematika di SD Negeri 2 Neglasari Tasikmalaya - Asep Eka Nugraha; Suyatmin (IAI Al Khoziny Buduran Sidoarjo, 2021)
The purpose of this study is to improve students' learning outcomes and learning activities in math subjects using demonstration methods. This study uses a class action research approach. This research was conducted as many as two cycles. The instruments used are, (1) Teacher performance observation sheet, (2) student activity sheet, (3) student learning result sheet. This instrument serves to collect research data. The results showed that in cycle I in learning planning obtained 3.08% and in cycle II the average score reached 3.11% with an increase of 0.3%. In the implementation of learning in cycle I the value obtained by 3.71% and in cycle II reached 3.59% with an increase of 0.12%. Then in the student learning outcomes in cycle I obtained 63.64% while in cycle II obtained 71.21%, with an increase of 7.57%. Data obtained from student activity in cycle I averaged 67.87% and average cycle II score of 72.12%, with an increase of 5.05%. During the learning process, in the first and second cycle students show high learning motivation that affects the achievement of learning outcomes. Thus the implementation of this class action research until the second cycle, and declared successful.